Cognitive processes involved in reading and writing for children of third grade of elementary school in Lima and Piura - Dioses Chocano, Alejandro (2010)
It was investigated, in students of the third grade of elementary school of Metropolitan Lima and Piura, if there were significant differences in the development of cognitive processes involved in reading and writing, considering the variables of gender, socioeconomic status, school management and town of residence. To gather data, it was adapted previously a Battery of Cognitive Assessment for Reading and Writing, establishing its reliability and validity. The results indicated differences in the cognitive processes examined in view of the variables, socioeconomic status, management of the school and town of residence.